Some murders in Berlin [large type] - Robards, Karen (Thorndike Press large print top shelf., 2024)
"September 1943. Berlin is the last place Dr. Elin Lund wishes to be. An expert in psychological profiling, she's been summoned from Copenhagen to investigate the gruesome murders of eight young women. Even in the midst of unspeakable evil, these killings stand apart. And with her homeland now under Nazi occupation and a young son to protect, Elin can't refuse such a request. Racing to complete the investigation and return to her son, Elin feels the net tightening. Every sliver of evidence reveals a killer infinitely more dangerous, and more powerful, than anyone suspected. And in drawing closer to the terrifying truth, Elin has unwittingly made herself his new obsession"--